Impact of extracardiac pathology on head growth in fetuses with congenital heart defect - van Nisselrooij, A. E. L. (Ultrasound Obstet Gynecol, 2019)
OBJECTIVE: Neurodevelopmental delay is frequently encountered in children with a congenital heart defect (CHD). Fetuses with major CHD have a smaller head circumference (HC), irrespective of altered cerebral flow or brain oxygenation. This cohort study compared head growth in cases with isolated vs those with non‐isolated CHD to evaluate the effect of additional pathology on head size in these fetuses. METHOD: All CHD cases diagnosed prenatally in the period January 2002–July 2014 were selected from our regional registry, PRECOR. Cases of multiple pregnancy, and those affected by maternal diabetes, severe fetal structural brain anomalies or functional CHD were excluded. Subjects were divided into groups according to whether the CHD was isolated, and the non‐isolated group was subdivided into three groups: cases with genetic anomaly, extracardiac malformation or placental pathology. In both isolated and non‐isolated CHD groups, CHDs were also grouped according to their potential effect on aortic flow and oxygen saturation. Mean HC Z‐scores at 20 weeks and increase or decrease (Δ) of HC Z‐scores over the course of pregnancy were compared between isolated and non‐isolated groups, using mixed linear regression models. RESULTS: Included were 916 cases of CHD diagnosed prenatally, of which 378 (41.3%) were non‐isolated (37 with placental pathology, 217 with genetic anomaly and 124 with extracardiac malformation). At 20 weeks, non‐isolated cases had significantly lower HC Z‐scores than did isolated cases (Z‐score = –0.70 vs –0.03; P < 0.001) and head growth over the course of pregnancy showed a larger decrease in this group (Δ HC Z‐score = –0.03 vs –0.01 per week; P = 0.01). Cases with placental pathology had the lowest HC Z‐score at 20 weeks (Z‐score = –1.29) and the largest decrease in head growth (Δ HC Z‐score = –0.06 per week). In CHD subjects with a genetic diagnosis (Z‐score = –0.73; Δ HC Z‐score = –0.04 per week) and in those with an extracardiac malformation (Z‐score = –0.49; Δ HC Z‐score = –0.02 per week), HC Z‐scores were also lower compared with those in subjects with isolated CHD. CHDs that result in low oxygenation or flow to the brain were present more frequently in isolated than in non‐isolated cases. CONCLUSIONS: Smaller HC in fetuses with CHD appears to be associated strongly with additional pathology. Placental pathology and genetic anomaly in particular seem to be important contributors to restricted head growth. This effect appears to be irrespective of altered hemodynamics caused by the CHD. Previously reported smaller HC in CHD should, in our opinion, be attributed to additional pathology. Neurodevelopment studies in infants with CHD should, therefore, always differentiate between isolated and non‐isolated cases. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.